Facıal Morphology In Sagıttal Components Of Skeletal Open Bıte - Mirzen Arat; Haluk İşeri; Verda İşeri (Galenos Yayinevi, 1996)
This study was based upon the evaluation of morphology and etiology of skeletal open bite, regarding the sagittal skeletal components. The material consists of lateral cephalometric films of 49 girls and 22 boys who had skeletal open bite. None of them received orthodontic treatment formerly. The sample was grouped as skeletal Class I, II and III facial types according to the ANB angle. A total of twenty three morphologic variables were employed and the data was analyzed by multivariate statistical methods. The results of this study indicated that, dentofacial morphology differs in the sagittal components of skeletal open bite, and the differences were more obvious between the Class II and III groups. The findings of this study also indicated that in the skeletal Class I and II open bite groups posterior upper dentoalveolar height and lower incisor inclination, and in the skeletal Class III group naso-oro pharyngeal airway and gonial angle seemed to be important factors in the development of open bite.